Cruise Sector Challenges Making Progress in an Uncertain World - Gibson, Philip; Papathanassis, Alexis; Milde, Petra; SpringerLink (Online service) (Wiesbaden : Gabler Verlag, 2011)
The challenge for cruise operators is to come to terms with a changing world where the realities of the past are not constant. This textbook presents a compendium of important issues that were discussed at the 2nd International Cruise Conference in Plymouth (UK) between the 18th and 20th February 2010. The focus of the conference was to consider emerging issues, problems and solutions for the cruise industry at a time when trading conditions were perceived to be highly volatile.
Keywords: Economics; Industrial management; Economics/Management Science; Business/Management Science, general; Management/Business for Professionals